0756 A One Year Observational Early Access Pitolisant Study of Excessive Daytime Sleepiness in Narcolepsy. (27th May 2020) - Stultz, D J; Osburn, S; Burns, T; Stanley, N; Walton, R; Pawlowska-Wajswol, S J; Moomaw, S
Abstract: Introduction: Pitolisant is a H3 receptor antagonist/inverse agonist that has been FDA approved for excessive daytime sleepiness in narcolepsy at doses of either 17.8 mg or 35.6 mg per day. Methods: 13 patients (3 males and 10 females) were studied having an average age of 46.8 years, with the majority receiving a dose of 35.6 mg Pitolisant. One patient received 17.8 mg throughout the year, and another advanced after 6 months to the 35.6 mg dose due to hepatic issues. 12 of the patients were Caucasian and one was Asian. 100% of the patients had co-existing sleep and psychiatric disorders. 46% had co-existing sleep apnea and were on CPAP/BIPAP. 38.5% had a history of a head injury. 84.6% of the patients had associated cataplexy, 38% had sleep paralysis, 92% had disrupted nocturnal sleep, and 46% had hypnogogic hallucinations. Throughout the year the patients were monitored using the Epworth Sleepiness Scale (ESS). Nine patients completed the 12-month ESS scales. 12/13 were on other medications to treat narcolepsy prior to starting Pitolisant. 6/13 were on sodium oxybate, 7/13 were on an antidepressant, and 11/13 were on either a stimulant, modafanil, or armodafanil. Only one patient was on Pitolisant alone. Results: The patient's average ESS score at onset was 16.2 Statistically significant findings using paired t-tests were documented. After one-month ESS scores decreased to an average of 13.2 (t=2.38, 9df, P=.04). At 3 months it was 12.4 (t=2.81, 10df, P=.02), at 6 months it was 12.75 (t=4.69, 11df, P<.001) and at 12 months the average score was 13.11 (t=2.55, 8df, P=.03) documenting clinically meaningful decrease of ESS by >/= 3 points. Three patients had ESS scores </=10 at 12 months. Conclusion: Improvement on ESS was documented at one month and sustained for one year in patients diagnosed with having narcolepsy both with and without cataplexy. Support: **No support was given for this study. Dr. Stultz is a speaker for Harmony Biosciences and has served on their advisory committee. She is also a speaker for Jazz Pharmaceuticals.